Harmonisation of Osmolal Gap – Can We Use a Common Formula? - Choy, Kay Weng (Clin Biochem Rev, 2016)
Osmolal gap is the difference between the measured osmolality and a calculated osmolality based on the major commonly measured osmotically active particles. The perceived gap indicates the presence of unmeasured osmotically active particles. The major use of osmolal gap today is to screen for the possible presence of exogenous toxic substances in patients in an emergency department or intensive care unit. There is a long history of osmolal gap calculations and it needs to be appreciated that the uncertainty of the osmolal gap will be determined by the sum of errors in the calculated osmolality, error in measured osmolality and variability in unmeasured analytes. Since 1958 there has been a constant trickle of papers proposing both simple and sophisticated formulae to calculate the ‘ultimate’ osmolal gap. A gap as close to zero as possible and with a low coefficient of variation across multiple clinical conditions and analytical platforms are also determinants of ‘fitness for purpose’ of any osmolal gap calculations. The Smithline-Gardner formula for calculated osmolality [2(Na) + Glu + Urea] is fit for purpose in both normal people and general hospital patients. It also performs well across different analytical platforms. This simple formula can be used for rapid mental calculation at the bedside and automated laboratory information system reporting whenever a measured osmolality is requested. In this era of harmonisation, we propose that this formula be adopted by all clinicians and laboratories.